The Stress and Coping Strategies in Nurses of a Tertiary Hospital, Punjab - Leghari, Shazia Yasmeen; Mukhtar, Madiha; Arshad, Sidra (Future Science, 2020)
Introduction: Stress is a non-specific reaction over organic entities initiated. Adapting for stress (coping) may be portrayed concerning illustration that fruitful management from claiming issues and particular distressing circumstances. The aim of this study is to assess the level of stress and coping strategies in nurses working at DHQ teaching hospital Dera ghazi khan Punjab Pakistan. Method: In this study, quantitative cross-sectional study design is used. A self-administered questionnaire was designed to assess the job-related stress level and coping strategies among nurses. The data was analyzed by SPSS version-18. Results: Out of 100 nurses, only (02) 2% nurses show severe level of stress, (76) 76% show moderate level of stress and remaining (22) 22% were mildly stressed. The level of stress attains maximum value r = +1, the coping strategy is r = 0.218 in one-tailed in term of two-tail its value become .030 having negative correlation one variable increase other decreased and vice versa. Conclusions: This study concluded that as the coping level of nurse’s increase the stress level goes down and when nurses fail to cope the stress level become increased. The night shift enhances the work load and cause stress and qualified nurses cope with stress more effectively than diploma holders.